Preparation and Properties of Soybean Oil Microemulsion Ice Slurry - Wu Xin; Sun Zhigao (Zhileng xuebao)
Ice slurry has good application prospects owing to its good cold thermal energy storage capacity and flow heat transfer ability. In this study, soybean oil microemulsionswere prepared using the Shah method, where soybean oil was used as the oil phase, Tween80 and AEO-3 as surfactants, and amyl alcohol as a cosurfactant. The influence of the mass ratio of the oil phase to the surfactant, HLB value of the surfactant, and mass ratio of surfactant to cosurfactant (Km value) on the water increase in the microemulsion was investigated experimentally. The optimum ratio of the microemulsion was obtained, where the mass ratio of the oil phase to surfactant, the mass ratio of Tween80 to AEO-3, and the Km valuewere 1:4, 6:4 (HLB value 11.6), and 2:1, respectively. The properties and structure of the microemulsions were analyzed in terms of particle size, electrical conductivity, and stability. Ice slurry was prepared using the microemulsion. The ice storage rate, apparent viscosity, and cycle stability of the ice slurry prepared using the microemulsion were tested and analyzed. The experimental results show that the soybean oil microemulsion with 50% water content isa W/O microemulsion with good stability. The prepared microemulsion ice slurry exhibitsa good ice storage rate and fluidity.